보행식 배추수확용 시작기 개발 및 성능시험 (Ⅰ) - 양규원; 박성진; 박우준; 김명신; 문병은; 김혁주; Kyu-Won Yang; Seong-Jin Park; Woo-Jun Park; Myeong-Sin Kim; Byeong-Eun Moon; Hyuck-Joo Kim (농업생명과학연구, 2022)
본 연구에서는 비닐멀칭된 외두둑에서의 배추 수확을 위한 시작기(A, B-1, B-2)를 설계 및 제작하였고, 시험을 통해 배추 수확을 위한 인발 장치부, 절단 장치부, 이송 장치부 등의 작업공정별 성능과 전체 작업성능을 분석하였다. 이론 분석을 통해 작업속도 0.2 m/s, 이송 벨트 각도 20∼35°, 이론적 이송 벨트의 적정 이송 속도를 작업속도보다 1.5배 빠르게 설정하여 청풍 및 춘광 품종을 대상으로 현장시험을 실시하였다. A형 시험 결과, 인발⋅이송성능은 성공률이 50% 수준으로 낮았으며, 절단성능의 경우 배추의 상품성이 양호한 경우가 35%, 과절단된 경우가 10% 및 미절단된 경우가 55%로 전반적으로 배추의 절단상태가 불량하였다. B형 시험 결과, 스핀들 인발장치는 비닐멀칭된 두둑에서는 감김현상으로 작업이 불가하였으며, 비닐멀칭없는 두둑에서의 인발⋅이송성능은 성공률이 78% 수준으로 A형보다 높아졌으나, 절단성능의 경우 배추의 상품성이 양호한 경우가 7.7%, 과절단된 경우가 15.4% 및 미절단된 경우가 76.9% 로 오히려 배추 절단상태는 더욱 불량해진 것으로 나타났다. 본 시작기의 비닐멀칭된 두둑에서의 현장시험 결과, 배추 인발, 절단 및 이송성능이 불량하게 나타나 인발, 절단, 이송작업에서의 전반적인 구조개선이 필요한 것으로 판단되었다. In this study, the prototype of walking type chinese cabbage harvester (A, B-1, B-2 type) were designed and manufactured for harvesting, and the pick-up device, cutting device, and conveying device and harvesting performance was tested at the vinyl-mulched single ridge. Field tests were conducted with Cheongpung and Chungwang varieties by setting the working speed of 0.2 m/s, the conveying belt angle of 20° to 35°, and the theoretical conveying belt 1.5 times faster than the working speed. As a result of the A-type test, the success rate in pick-up and transporting performance was as low as 50%, and in terms of cutting performance, the quality of cabbage cut section was good in 35%, overcut in 10%, and uncut in 55%, overall. As a result, the cabbage cut quality and conveying performance was poor. As a result of the B-type test, the spindle pick-up device was unable to work due to the winding troubles on the ridges with vinyl mulching, and the success rate of the pick-up/conveying performance without vinyl mulching was 78% which is higher than that of Type A. But in the case of cutting performance, the result was 7.7% of the good quality of cabbage cut section, 15.4% of over-cut and 76.9% of uncut, which showed that the cut quality of Chinese cabbage was rather poor. Therefore, as a result of the field test in the vinyl-mulched ridge of this initial stage, the extraction, cutting and transfer performance of Chinese cabbage was poor, and it was determined that overall improvement in the pick-up, cutting, and conveying operation was necessary.